Update on cholangiocarcinoma: potential impact of genomic studies on clinical management - Walter, Dirk; Hartmann, Sylvia; Waidmann, Oliver (Zeitschrift für Gastroenterologie, 2017)
The term cholangiocarcinoma (CCA) comprises neoplasms of the intrahepatic, perihilar, and distal bile duct. Five-year survival rates of patients with CCA are below 20 %, and no targeted therapy could prove a benefit in comparison to the standard treatment of cisplatinum and gemcitabine. In recent years, next generation sequencing studies revealed a profound genomic heterogeneity of CCA subtypes potentially affecting the design of future therapy trials. This review provides a concise update on current clinical management of CCA including data of recent genomic studies and differences between CCA subtypes.
Keywords: Cholangiokarzinom; Gallengangstrakt; Genetik; next generation sequencing; gezielte Therapien; immunmodulatorische Therapien